2018
DOI: 10.13189/ujer.2018.060907
|View full text |Cite
|
Sign up to set email alerts
|

Education and Career Choices: How the School Can Support Young People to Develop Knowledge and Decision-making Skills

Abstract: Contemporary society is characterized by rapid changes in the labor market, increased flow of information, and more opportunities to make choices in relation to education and career. Previous research has demonstrated how many young people in school don't think they get the support they need to make such choices. The overall aim of this article is to contribute to more in-depth knowledge of what kind of support and knowledge young adults describe as important in order to be able to make informed choices. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…Everyone has the same career opportunities and choices according to the abilities they have. So that students need to get support in choosing an appropriate career [36]. One of the services that can help students make the right career choice is counseling that focuses on solutions.…”
Section: Resultsmentioning
confidence: 99%
“…Everyone has the same career opportunities and choices according to the abilities they have. So that students need to get support in choosing an appropriate career [36]. One of the services that can help students make the right career choice is counseling that focuses on solutions.…”
Section: Resultsmentioning
confidence: 99%
“…Students are prepared to be able to find out the career goals and jobs they want to do in the future. (Eriksson et al, 2018) revealed that classical career guidance activities that aim to contribute to knowledge about the labor market, programs and courses and requirements for different educational programs might be considered more beneficial by young adults if they are organized in a combination of various level, academic. Both as group activities (exhibitions, general information / discussion) and individual activities (personal information / discussions).…”
Section: Discussionmentioning
confidence: 99%
“…Studies also show that study guidance plays a crucial role in students choosing education in a different field than expected (Borghans et al, 2015). However, research by Eriksson et al (2018) shows that there are sometimes problems with study guidance, with students without an academic background describing a lack of information about higher education and only receiving information about vocational education. According to the authors, this risk leads to unequal class structures being reproduced, so that the choice of education is not expanded with new perspectives but is limited to students' own knowledge of the labour market and the knowledge they gain from their families.…”
Section: Previous Researchmentioning
confidence: 99%
“…These adult students view further studies as a possibility, but they lack important information about how to pursue such studies. Like Eriksson et al (2018), we see a risk that this lack of information is leading to a reproduction of unequal class structures, where working class adults get working class jobs.…”
Section: Comparing Choices and Pathwaysmentioning
confidence: 99%